The application of exosomes in the early diagnosis and treatment of osteoarthritis - Chen, Anjing; Chen, Yangmengfan; Rong, Xiao; You, Xuanhe; Wu, Diwei; Zhou, Xinran; Zeng, Weinan; Zhou, Zongke (Frontiers in Pharmacology, 2023)
With the increase in human life span and the aggravation of global aging, the incidence of osteoarthritis (OA) is increasing year by year. The pain and dysfunction caused by OA affect the quality of work and life of patients with end-stage arthritis seriously. At present, there is no specific treatment for OA progression; and joint replacement is the only choice for end-stage arthritis patients. Therefore, effective remission of the pains and delay in the development of OA have been a primary concern. Doctors and scientists hope to explore the pathogenesis of osteoarthritis furtherly, develop more sensitive diagnostic methods, and find specific markers for different stages of the disease; these efforts will help shift the focus toward the comprehensive prevention and treatment of osteoarthritis. Exosomes are a class of extracellular vesicles containing bioactive substances that can be delivered directly from cells to neighboring cells or via peripheral circulation to distant cells for intercellular communication. In the past decade, it has been found that exosomes play an important role in the regulation of an organism's internal processes, including tissue repair. Exosomes are also involved in the development of OA disease and play a regulatory role between immune and non-immune cells in the joints. In addition, specific molecules carried by the exosomes secreted into fluids in OA regions can be used in the early diagnosis of OA, which is of great significance for prevention and treatment. This article focuses on the potential of exosomes in osteoarthritis.